Developing Ethical Awareness in Global Health: Four Cases for Medical Educators. Issue 3 (1st October 2012) - White, Mary; Evert, Jessica
Abstract In recent years, the growth of interest in global health among medical students and residents has led to an abundance of short‐term training opportunities in low‐resource environments. Given the disparities in resources, needs and expectations between visitors and their hosts, these experiences can raise complex ethical concerns. Recent calls for best practices and ethical guidelines indicate a need for the development of ethical awareness among medical trainees, their sponsoring and host institutions, and supervising faculty. As a teaching tool to promote this awareness, we developed a scenario that captures many common ethical issues from four different perspectives. Each perspective is presented in case format followed by questions. Taken together, the four cases may be used to identify many of the elements of a well‐designed global health training experience.